HOW AUDITOR-ORIENTED EMPLOYEE PERFORMANCE MANAGEMENT AFFECTS INTERNAL AUDIT EFFECTIVENESS BY REDUCING ITS CONSTRAINTS - Lena GRZESIAK; Wojciech ULRYCH (Humanities and Social Sciences)
This manuscript aims to determine how audit-oriented employee performance management (A-OEPM) practices influence internal audit effectiveness (IAE) mediated by internal audit constraints (IAC). The study was conducted in late 2021 by using a quantitative approach (CAWI method). In this type of practice, managers are not engaged in employee development, and they use management by objective method instead of EPM. They exclude team-oriented practices from the A-OEPM-IAE relations. Neither a job description tool nor a career development plan was used. Instead, only the practices that support up-to-date IA tasks and responsibilities are important for managerial decisions. The paper fills a gap in management literature by examining the relationships between A-OEPM, IAC, and IAE. In order to overcome the IAC, the A-OEPM could be a valuable tool to help both parties implement organizational changes necessary to achieve IAE.